Peningkatan produksi biogas dari palm oil mill effluent (POME) dengan fluidisasi media zeolit termodifikasi pada sistem batch - Firda Mahira Alfiata Chusna; Melly Mellyanawaty; Estin Noviyanti (Jurnal Rekayasa Proses, 2020)
The production of crude palm oil (CPO) in Indonesia tends to increase over time. Palm oil mill effluent (POME) is the wastewater generated from the palm oil mill process with high organic content. POME is a potential source for anaerobic digestion due to its high organic content. The challenge of POME treatment using an anaerobic process is to enhance biogas production with high soluble chemical oxygen demand (sCOD) removal efficiency. The purpose of this study was to evaluate the effect of selected trace elements addition onto zeolite as immobilization media to the anaerobic digestion of POME in a fluidized batch system. Natural zeolite was used as the medium to immobilize microorganisms in an anaerobic fluidized bed reactor (AFBR). This study used three trace elements impregnated to natural zeolites, i.e. Ni2+, Zn2+, Mg2+. The result shows that Ni2+ and Zn2+improve the methanogenesis process, prevent the accumulation of VFA as an intermediate product and increase the methane (biogas) production. Meanwhile, Mg2+ only reduced sCOD significantly but it did not affect methane production. Fluidization enhanced the performance of the POME anaerobic digestion process. The fluidization provide a positive effect to enhance biogas production and sCOD removal. The efficiency of sCOD removal in the entire reactors were 80.82%; 81.77%; 75.89% for AFBR-Ni; AFBR-Zn and AFBR-control respectively. The total volume of methane produced by the three AFBR were 163,04; 136,42; 62,79 (in ml CH4 / g sCOD) for AFBR-Ni; AFBR-Zn and AFBR-control, respectively.